Strategi Komunikasi Politik Rayhan Muhammad Handoko dalam Pemilihan Legislatif DPRD Kabupaten Banyuasin 2024 - Budimantoro Budimantoro; Desy Misnawati (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The 2024 Legislative Election at the regional level demands that candidates possess communication strategies that are not only persuasive but also credible. This study aims to analyze the political communication strategies employed by Rayhan Muhammad Handoko from the Prosperous Justice Party (PKS) in securing a seat in the Banyuasin Regency Regional House of Representatives (DPRD) during the 2024 Election. The primary problem of this research focuses on the effectiveness of managing political messages amidst a critical electorate. Drawing upon the framework of Ariton-Gelan (2015), this study emphasizes that in argumentative and persuasive situations, a communicator bears a moral obligation to verify the validity of evidence and arguments before presenting them to the public. The research method used is descriptive qualitative, utilizing in-depth interviews, observation, and documentation studies. The findings indicate that Rayhan Muhammad Handoko’s success was driven by the implementation of a communication strategy based on validated data and measurable political promises, integrated through digital political branding and interpersonal door-to-door approaches. The synchronization between valid messaging and the actual needs of constituents became a determining factor in gaining voter trust. This research contributes to the development of political communication science, particularly regarding the importance of communication ethics and argumentative validity in winning local voter sympathy. This success proves that persuasive communication grounded in moral responsibility toward message content is a key determinant in modern political campaigning.